Kinerja bahan isolasi non keramik di daerah tropis - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
Non-ceramic insulatos have been increasingly accepted by industry and utilities to replace porcelain and glass insulators because of the well-known advantages the non ceramic insulators have, such as light weight, ease of handling, reduce installation and maintenance cost, vandalism resistance, and inproved contamination performance. How ever, non-ceramic insulation material, likes epoxy resin has some disadvantages. It is very sensitive, if it used in high temperature and in a very humid areas, and also in area where exist high intensity of ultraviolet radiation. These climates condition unfortunately found in most area in Indonesia which will cause leakage current then develops which may lead tq flashover that could be followed by an outage of the power system. In order to reduce the incidence of non-ceramic insulator flashover, this paper presents the results of an investigationon the electrical performance of artificially contaminated epoxy resin insulation material. The specimens of epoxy resin insulating materials are based on diglysidil ether of bisfenol-A (dgeba), metaphenylene-diamine (mpda) as curing agent, and silica filler were used. Part of specimens is coating by silicon compound Experimental method was carried out through the following procedure : (I) the contaminant coating on specimen surface in fog chamber and simulation of ultra violet radiation, (2) the ac voltage was applied between two electrodes inserted into specimen surface, (3) the measurement of leakage current on contamination specimens surface, and (4) the calculation of equivalent salt deposit density (esdd) On the basis of the results, it can be concluded the increase both esdd and uv radiation on the specimens surface cause the increase of leakage current. Silicone compound coating on specimen surface is able to suppress the development of leakage current.